Factors Influencing the Decision of Migration to Southern Region of the Population in Thailand through a Binary Logistic Regression Model - Janmanee, Kamonthip; Ratilertkul, Maneerat; Thiuthad, Phontita (JOURNAL OF SOUTHERN TECHNOLOGY, 2024)
Migration involves the relocation of individuals' residences, which affects the demographic structure due to variations in population size across different areas, potentially leading to various problems. In 2021, the southern region of Thailand experienced the highest migration rate, reaching 1.2% of the total population. This research aimed to study the personal factors influencing migration to the southern region of Thailand and to develop a model predicting the probability of migration to this area. The study used a sample of 1,258 individuals and examined factors affecting the migration such as gender, age, marital status, education level, occupation, current province of residence, administrative district, household size, relationship to the household head, hometown, monthly income, and primary reason for migration. The chi-squared test was employed to examine the relationship between these factors and migration, and binary logistic regression analysis was conducted to develop a model predicting migration probability in the southern region. The analysis of personal factors using the chi-squared test revealed that factors of age, current province of residence, administrative district, relationship to the household head, monthly income, and primary reason for migration significantly correlate with migration to the southern region. The logistic regression analysis indicates that the prediction model could accurately forecast migration to the southern region 66.5% of the time. Furthermore, the study found that most migrants were unemployed and had no income, suggesting that relevant agencies could use this information to manage, assist, and address these issues effectively.